IMPACT OF NUCLEOTIDES ON THE FORMATION OF THE LOCAL INTESTINE IMMUNITY AMONG CHILDREN - I.N. Zakharova; N.A. Korovina; E.V. Lykina ("Paediatrician" Publishers LLC, 2007)
The article highlights the issue of the effects of the nucleotides, being a part of the modern artificial mixtures, on the state of the local immunity among children. The authors present the literature data, witnessing the close interrelation between the feeding and level of secretory immunoglobulin a (SIgA) in coprofiltrates. They also present the data of their own research based on the dynamic observation of 85 clinically healthy infants aged between 1 and 4 months. The article demonstrates the clear dependence of the SIgA level upon the character of the infant feeding. Key words: infants, feeding, nucleotides, secretory immunoglobulin A, coprofiltrates, local immunity, intestine microbiocenosis.